2015
DOI: 10.1093/toxsci/kfv038
|View full text |Cite
|
Sign up to set email alerts
|

Urinary ATP Synthase Subunit β Is a Novel Biomarker of Renal Mitochondrial Dysfunction in Acute Kidney Injury

Abstract: Although the importance of mitochondrial dysfunction in acute kidney injury (AKI) has been documented, noninvasive early biomarkers of mitochondrial damage are needed. We examined urinary ATP synthase subunit β (ATPSβ) as a biomarker of renal mitochondrial dysfunction during AKI. Mice underwent sham surgery or varying degrees (5, 10, or 15 min ischemia) of ischemia/reperfusion (I/R)-induced AKI. Serum creatinine, BUN, and neutrophil gelatinase-associated lipocalin were elevated only in the 15 min I/R group at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Cytochrome c is a poor renal biomarker as it is only transiently elevated following injury and thus likely serves as a better predictor of degree of renal damage rather than recovery and disease progression. Our group recently reported that urinary levels of the ATP synthase subunit β serve as a biomarker of CPB-induced AKI and I/R-induced AKI in mice; however, the predictive value in this study was not assessed 28 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Cytochrome c is a poor renal biomarker as it is only transiently elevated following injury and thus likely serves as a better predictor of degree of renal damage rather than recovery and disease progression. Our group recently reported that urinary levels of the ATP synthase subunit β serve as a biomarker of CPB-induced AKI and I/R-induced AKI in mice; however, the predictive value in this study was not assessed 28 .…”
Section: Discussionmentioning
confidence: 77%
“…To explore the biological correlates of UmtDNA in the kidney, we used a mouse model of renal I/R injury. Mice were subjected to sham surgery (n=12) or bilateral renal pedicle ligation for 5 (n=4), 10 (n=9) or 15 min (n=11) corresponding to mild, moderate and severe renal histological damage 28 . Mice that produced no or insufficient urine for detection of UmtDNA (n=6) were excluded from further analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent to this a decrease in ALR was observed, in line with the decrease in cellular ATP-content observed. Using the framework postulated by Kamalian et al for the mechanistic interpretation of Seahorse data, a decrease in ALR and SRC occurring in tandem with a decrease in BR indicates that FIAU inhibits activity of the electron transport chain ( Whitaker et al, 2015 ; Ball et al, 2016 ; Kamalian et al, 2018 ). Further analysis offers additional mechanistic insight.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found significant correlation between the CIT and the levels of mitochondrial hydroxyl acyl coenzyme A dehydrogenase and ATP synthase subunit beta which suggests an increase in mitochondrial disruption with CIT. Whitaker et al have recently shown increased urinary ATP synthase subunit beta in mice with renal injury and concluded that urinary ATP synthase subunit beta may be a novel and sensitive biomarker of renal mitochondrial dysfunction [37]. …”
Section: Discussionmentioning
confidence: 99%